CLEANING VALIDATION OF A SIMPLE AND RAPID REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE SIMULTANEOUS ESTIMATION OF ASPIRIN AND ROSUVASTATIN - NAZARETH, CELINA; FIZARDO, GISELLE; VAZ, CHARMAINE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study describes a new, simple, precise, accurate, and reproducible reversed-phase high-performance liquid chromatography (RP-HPLC) cleaning validation method for simultaneous estimation of rosuvastatin and aspirin. Methods: The proposed RP-HPLC method was carried out on AGILENT-ZORBAX RP-Inertsil column (250 mm × 4.6 mm, 5 μm) in an isocratic mode utilizing potassium dihydrogen phosphate buffer (pH 2.5 with OPA):acetonitrile (50:50,v/v) as mobile phase, at a flow rate of 1.5 ml/min. Detection was carried out at 243 nm using UV detector. Results: The method was found specific as there was no swab interference. The Beer–Lambert’s law was obeyed in the concentration range of 0.5–20 μg/ml for both rosuvastatin and aspirin. The mean percentage recoveries at 100% level were 89.4% for rosuvastatin and 82.1% for aspirin. The limit of detection and limit of quantification for rosuvastatin and aspirin were 0.03 μg/ml and 0.1 μg/ml, respectively. The method was found to be robust and precise with percentage RSD <2.0%. Conclusion: A simple, novel, and economical RP-HPLC method for cleaning validation has been developed for the simultaneous estimation of rosuvastatin and aspirin. The method was validated as per ICH guidelines for specificity, linearity, accuracy, precision, and robustness. The developed method can be used as a sensitive analytical tool for ensuring the effectiveness of the cleaning procedure adopted.